Genetic Mutations Affecting the Respiratory Electron-Transport System of the Photosynthetic Bacterium Rhodopseudomonas capsulata - Marrs, Barry (1973)
Alternative energy-converting systems permit the nonsulfur purple photosynthetic bacterium Rhodopseudomonas capsulata to grow either with light or (dark) respiration as the source of energy. Respiratory mutants, unable to grow aerobically in darkness, can be readily isolated and the defective step(s) in their respiratory mechanisms can be identified by study of biochemical activities in membrane fragments derived from photosynthetically grown cells. Such analysis of appropriate mutants and revertants permits construction of a model for the respiratory electron-transport system of the wild type. The results obtained indicate differential channeling of electrons derived from succinate and reduced nicotinamide adenine dinucleotide, and are interpreted in terms of a branched electron-transport scheme. The scheme provides a guide for further, more refined analysis of the respiratory mechanisms through biochemical genetic approaches, and several of the mutants isolated can be exploited for investigation of unsolved problems relating to interactions between respiratory and photosynthetic electron transport and the mechanism of inhibition of bacteriochlorophyll synthesis by molecular oxygen.